Implementasi Fundamental Movement Skills (FMS) Pada Anak Usia Sekolah Dasar - Muhammad Harliawan; Imam Suyudi; Andi Ridwan; Awaluddin (LITERA ABDI: Jurnal Pengabdian Masyarakat, 2025)
Child growth and development is something complex. This means that there are many factors that influence and are interconnected in the process of child growth and development, basic child movement refers to efforts to help children in developing basic motor and movement skills, Fundamental Movement Skills (FMS) are basic movement skills that are the foundation for doing more complex physical activities, such as sports or daily activities. FMS helps someone develop the physical abilities needed to move efficiently and safely. The purpose of this service is to provide children with an understanding of basic movements that are the foundation for more complex sports and physical activity skills, the method used is the game method, the results of this service are increased motor coordination abilities, increased balance and stability in students, increased flexibility and mobility, improved mental and physical coordination, increased cooperation and social skills, increased physical strength, increased concentration and focus and increased discipline.